Chemical Composition of Litsea pungens Essential Oil and Its Potential Antioxidant and Antimicrobial Activities - Tao Chen; Qingbo Kong; Xuekun Kuang; Jiasi Zhou; Haizhou Wang; Lijun Zhou; Hongyu Yang; Shiling Feng; Chunbang Ding (Molecules, 2023)
Litsea pungens is a plant with medicinal and edible properties, where the fruits are edible and the leaves have medicinal properties. However, there is limited research on the chemical and pharmacological activities of the plant. In this study, essential oils were extracted by steam distillation and their antioxidant and antibacterial activities were further evaluated. Gas chromatography–mass spectrometry (GC–MS) was used to identify the chemical components of L. pungens fresh fruit essential oil (FREO) and L. pungens fresh flower essential oil (FLEO), rapeseed oil (RO) and commercial Litsea oil (CEO). The results showed that 12 chemical components were identified in FREO. Twelve chemical components were identified from FLEO, four chemical components were identified from CEO, and thirteen chemical components were identified from RO. Except for RO, the other three oils were mainly composed of terpenes, among which limonene is the main chemical component. In terms of antioxidant activity, FREO, FLEO, CEO and RO have antioxidant capacity, mainly reflected in the scavenging DPPH free radicals and the iron ion chelating ability, and the antioxidant activity shows a certain dose effect, but the antioxidant activity of FLEO is the weakest among the four oils. Meanwhile, under the stress of hydrogen peroxide, CEO demonstrated a significant antioxidant protective effect on cells. It is worth mentioning that compared with the positive control, the FREO exhibited a better antibacterial rate. When the concentration of essential oil is 20 mg/mL, the bacteriostatic rate can reach 100%. Therefore, it could be a promising candidate among medicinal and edible plants.